Activity of rifampicin and linezolid combination in Mycobacterium tuberculosis - Maltempe, Flaviane Granero (2017)
Background: Linezolid (LZD) is not commonly used for treating tuberculosis (TB), but in some patients with drug-resistant TB it is being used. However, the in vitro LZD activity, in combination with rifampicin (RIF) against Mycobacterium tuberculosis has not been fully elucidated. Aims: The aim of this study was to evaluate the in vitro activity of RIF/LZD combination against M. tuberculosis clinical isolates. Materials and methods: The activity of the RIF/LZD combination was firstly determined in M. tuberculosis H(37)Rv, 14 susceptible, 9 isoniazid nonresistant and 14 multi-drug resistant (MDR) M. tuberculosis clinical isolates by modified checkerboard assay, Resazurin Drugs Combination Microtiter Assay (REDCA). After, the Time Kill Curve Assay, at 0.5 x MIC of drugs, in combination and alone, was performed in M. tuberculosis H(37)Rv and 8 (20.5%) of those clinical isolates, which the RIF/LZD combination showed to have synergistic effect by the checkerboard assay. Results and conclusion: By Time Kill Curve Assay, we could observe in M. tuberculosis H(37)Rv and susceptible isolates, that LZD alone, at sub inhibitory concentration, has poor effect on the bacillus death. In some cases, the bacillus growth stayed constant while in others showed regrowth at the eighth day of drug exposure. RIF alone exhibits potent concentration-dependent bactericidal activity, and was strongly dependent by the drug exposure time. The RIF/LZD combination accomplished a bacteriostatic effect in the reference strain and susceptible isolates. For the RIF resistant isolates, the RIF/LZD combination did not enhance the effect in killing bacillus. In this sense, additional, in vitro and in vivo studies are needed to evaluate the effect of RIF/LZD combination in order to better understand the adjunctive action of LZD in the treatment of TB and prevent the emergence of mutants with resistance to the available anti-TB drugs. (C) 2017 Elsevier Ltd. All rights reserved.